Maternal overweight and sexual function in pregnancy - Ribeiro, Meireluci C.; Nakamura, Mary U.; Torloni, Maria R.; Scanavino, Marco De T. [UNESP]; Mancini, Pedro E.; Forte, Bruna M. B.; Mattar, Rosiane (Wiley-Blackwell, 2016)
IntroductionObesity and overweight are increasing worldwide and may compromise female sexual function. Our aim was to compare the sexual function of normal and overweight women in pregnancy. Material and methodsA cross-sectional study involving 223 pregnant women: 105 overweight [pre-pregnancy body mass index (BMI) 25.0 kg/m(2)] and 118 normal weight (BMI 18.5-24.9 kg/m(2)), in the 2nd and 3rd trimester of pregnancy. These women were managed at an antenatal clinic of a public university hospital in SAo Paulo, Brazil, between 2011 and 2014. The Female Sexual Function Index (FSFI) was used. The characteristics of normal and overweight women were compared using two-tailed Student's t- or chi-squared tests. Differences in mean FSFI scores were assessed using the Kruskal-Wallis test. Pearsons correlation coefficient was used to assess the correlation between pre-pregnancy BMI and FSFI scores. ResultsIn the 2nd trimester, mean total FSFI scores were similar in overweight (n = 51) compared to normal weight (n = 67) women (21.9 9.8 vs. 21.7 +/- 10.4, p = 1.000). In the 3rd trimester, overweight women (n = 54) had significantly lower total FSFI scores than normal weight women (n = 51; 19.1 +/- 10.3 vs. 24.5 +/- 9.7, p = 0.0004). In the 3rd trimester, overweight women also had significantly lower mean scores in desire, arousal, lubrication, orgasm and dyspareunia domains. We found an inverse correlation between pre-pregnancy BMI and mean 3rd trimester total FSFI scores (r = -0.212, p = 0.030), desire (r = -0.216, p = 0.027) and orgasm (r = -0.222, p = 0.023). ConclusionOverweight women in the 3rd trimester of pregnancy had poorer sexual function compared with normal weight women.
Keywords: Pregnancy; sexual dysfunction; sexuality; overweight; obesity